O071 An innovative prone contrast enhancement computed tomography angiography (PASHA) protocol to diagnose concealed endoleak and aortic sac hygroma. (22nd July 2022) - Sultan, S; Acharya, Y; Hynes, N
Abstract: Introduction: Standard 4-phase supine computed tomography angiography (CTA) scans are unable to detect smaller fabric tear (< 1–2 mm) following EVAR, which are erroneously interpreted as type IV or V endoleak (EL). Here, we propose a novel diagnostic technique, 'Prone contrASt enhanced computed tomography Angiography' (PASHA)' that uses time-resolved four-phase CTA protocol to detect and classify concealed ELs. Methods: We employed PASHA protocol in 46 patients after continuous sac expansion following primary EVAR where the standard 4-phase CTA could not identify the EL source. PASHA protocol uses a prone position during standard 4-phase CTA, which displaces the aorta anteriorly by approximately 5 mm, shortening the anterior cortex distance and allowing fluid transudation due to gravity with maximal EL enhancements. Results: The average numbers of CT scans performed before diagnosing EL with PASHA protocol were 3.4 ±1.5 (range: 1–6). PASHA protocol demonstrated EL in all 46 cases that the standard supine 4-phase CTA could not identify. PASHA protocol effectively enhanced the degree of contrast infiltration into the aortic sac in all the patients. Conclusion: PASHA is a multi-phase positional CTA technique that enhances the degree of contrast infiltration into the aortic sac when micro-leaks are present, increasing the EL detection rate following EVAR and strategically mapping successful future intervention. Take-home message: Prone contrASt enHanced computed tomography Angiography (PASHA) is a multi-phase positional computed tomography angiography (CTA) technique that enhances the degree of contrast infiltration into the aortic sac when micro-leaks are present. PASHA increases the endoleak (EL) detection rate following endovascular aneurysm repair (EVAR) and strategically maps successful future interventions.